"Díaita": Lifestyle and Alterity in Xenophon’s Socrates - Sierra Martín, César (Logos. Anales del Seminario de Metafísica, 2018)
The aim of the present work is to analyze the Socrates’ lifestyle on Xenophon. We start from the definition of medical concepts such as díaita or dýnamis from pythagorics to the Corpus Hippocraticum. After that, we will study the impact of these ideas in the universal model of virtue and leadership built around Socrates and other figures.